Nanofiltration Hollow Fiber Membranes Made from Sulfonated Polysulfone having a Cyanophenylene Group - Higashi, Masao; Nakao, Takahito; Morita, Junsuke; Kitagawa, Tooru (Journal of Membrane and Separation Technology, 2016)
A nanofiltration hollow fiber membrane made from sulfonated polysulfone was proposed in this work to meet the demands of having tolerance against chemicals. The sulfonate group in the molecule is a source of highly hydrophilic properties and may increase the inter-molecular force acting between molecules on which it is attached. It also contributes to forming a tight structure in the membrane. The membrane may produce higher water flux than those of commercially available nanofiltration membranes made from polyamides. The state of water in the wet membrane was examined with a nuclear magnetic resonance spectrometer. The bonding force to confine water molecules in the membrane may be considered to control the water flux and salt rejection of membranes. It is revealed that there were two kinds of water in the membrane and the salt rejection was raised when the interaction to the water molecules from sulfonate groups in the sulfonated polysulfone molecule was increased. The salt rejection and water flux is highly correlated with the chemical shift of constrained water.